The birth of the Alps: Ediacaran to Paleozoic accretionary processes and crustal growth along the northern Gondwana margin - Siegesmund, Siegfried (2021)
New whole-rock geochemical and coupled U–Pb and Lu–Hf LA-ICP-MS zircon data of metasedimentary rocks of the Austroalpine, South Alpine and Penninic basement domains are presented, to disentangle the pre-Variscan tectonic evolution of the proto-Alps. The studied units seem to record distinct stages of protracted Late Ediacaran to Carboniferous tectonosedimentary processes prior to the Variscan collision. In the case of Austroalpine and South Alpine units, nevertheless, no major differences in terms of provenance are observed, since most detrital zircon samples are characterized by a major Pan-African peak. Their detrital zircon spectra record a provenance from the northeastern Saharan Metacraton and the Sinai basement at the northern Arabian-Nubian Shield, being thus located along the eastern Early Paleozoic northern Gondwana margin, whereas sources located further west are inferred for the Penninic Unit, which might have been placed close to the Moldanubian Unit of the Bohemian Massif. In any case, it is thus clear that the Alpine basement remained in a close position to the Gondwana mainland at least during the Early Paleozoic. The Late Ediacaran to Silurian tectonic evolution, which includes Cadomian and Cenerian tectonometamorphic and magmatic processes, seem thus to record a continuum related to a retreating-mode accretionary orogen, with diachronous back-arc basin opening and possibly discrete compressional/transpressional pulses linked to changes in subduction zone dynamics. On the other hand, it is inferred that the Alpine basement essentially comprises Pan-African metasedimentary and subordinate metaigneous rocks, possibly with very few Early Neoproterozoic relics. This basement was significantly reworked during the protracted Paleozoic orogenic evolution, due to anatexis and/or assimilation by mantle-derived juvenile magmatism.